Geometry, Algebra and Applications: From Mechanics to Cryptography - Castrillón López, Marco; Hernández Encinas, Luis; Martínez Gadea, Pedro; Rosado María, Mª Eugenia (Springer Proceedings in Mathematics & Statistics, 2016)
This volume collects contributions written by different experts in honor of Prof. Jaime Muñoz Masqué. It covers a wide variety of research topics, from differential geometry to algebra, but particularly focuses on the geometric formulation of variational calculus; geometric mechanics and field theories; symmetries and conservation laws of differential equations, and pseudo-Riemannian geometry of homogeneous spaces. It also discusses algebraic applications to cryptography and number theory. It offers state-of-the-art contributions in the context of current research trends. The final result is a challenging panoramic view of connecting problems that initially appear distant.